Noshing on Chocolate, I Can Do That: Increased Chocolate Consumption in the Chocolate‐Modified Bogus Taste Test With Better and Not Worse Inhibitory Control. - Schroeder, Philipp A.; Ernst, Anton; Wirth, Robert; Kroemer, Nils B.; Svaldi, Jennifer (European Eating Disorders Review, 2025)
Background: Chocolate is the most craved energy‐dense food. Yet, most individuals can limit their chocolate consumption. Here, we investigate the cognitive mechanisms underlying chocolate consumption in a chocolate bogus taste test in a cross‐sectional experimental design. Method: High chocolate cravers abstained from chocolate for a week, followed by a virtual reality chocolate exposure with biometric trajectory recordings of their stopping responses and an ad‐libitum bogus taste test of spontaneous chocolate intake. A single‐target implicit association task and a computerised stop‐signal task served as unstandardised control tasks 1–2 days before chocolate intake. Results: Associations of parameters from all tasks with chocolate intake were small (|r| < 0.23). Elastic net models misestimated food intake by min. 160 kcal (generalisation: 180 kcal) and feature selection was only possible with L1 penalty. At the group level, participants showed a more controlled and delayed movement towards chocolate relative to neutral cues, evidenced by lower peak acceleration and peak velocity and faster stopping latency. Discussion: The findings demonstrate the complex cognitive‐behavioural underpinnings of food intake, food craving and abstinence.